Pengaruh pH dan Kekuatan Ionik terhadap Profil Kelarutan Ofloksasin - BUDIPRATIWI WISUDYA NINGSIH; SUWALDI SUWALDI; AKHMAD KHARIS NUGROHO (Fakultas Farmasi Universitas Pancasila, 2014)
Ofloxacin is an antibiotic and categorized as class 2 in Biopharmaceutics Classification System (BCS). Ofloxacin solubility is dependent on pH of the solvent due to its amphoteric properties. The objectives of this research was to investigate the effects of pH and ionic strength on solubility profile of ofloxacin. Ofloxacin solubilities were measured at various pH ranged from 1.5 to 12.5 and ionic strengths from 0.01 to 0.20 respectively. Solubility experiments were carried out using shaking thermostatic-waterbath for 3 hours at a temperature of 37°C ± 1°C. Results showed that ofloxacin solubility increased at pH’s below the pKa1 value (6.08) and above the pKa2 value (8.25). However, the solubility decreased at pH’s between pKa1 and pKa2. Changing the solution pH from 6.2 to 1.5 or to 12.5 affected the solubility of ofloxacin increased about 9.96 and 8.64 times higher, respectively. Ofloxacin solubility in various ionic strengths showed that stronger ionic strength solution caused an increase in ofloxacin solubility. This mean that there was a salting in phenomena. Least-Square Fitting Analysis using Henderson-Hasselbalch equation for amphoteric compound was insufficient to describe ofloxacin solubility process in a series of pH.